Informed Consent and Shared Decision Making in Obstetrics and Gynecology: ACOG Committee Opinion Summary, Number 819. Issue 2 (February 2021) - N/A
Abstract : ABSTRACT: Meeting the ethical obligations of informed consent requires that an obstetrician–gynecologist gives the patient adequate, accurate, and understandable information and requires that the patient has the ability to understand and reason through this information and is free to ask questions and to make an intentional and voluntary choice, which may include refusal of care or treatment. Shared decision making is a patient-centered, individualized approach to the informed consent process that involves discussion of the benefits and risks of available treatment options in the context of a patient's values and priorities. Some informed consent challenges are universal to medicine, whereas other challenges arise more commonly in the practice of obstetrics and gynecology than in other specialty areas. This Committee Opinion focuses on informed consent for adult patients in clinical practice and provides new guidance on the practical application of informed consent through shared decision making. The principles outlined in this Committee Opinion will help support the obstetrician–gynecologist in the patient-centered informed consent process.